Capital structure, equity ownership and firm performance - Margaritis, Dimitris; Psillaki, Maria (Journal of Banking & Finance, 2010)
This paper investigates the relationship between capital structure, ownership structure and firm performance using a sample of French manufacturing firms. We employ non-parametric data envelopment analysis (DEA) methods to empirically construct the industry’s ‘best practice’ frontier and measure firm efficiency as the distance from that frontier. Using these performance measures we examine if more efficient firms choose more or less debt in their capital structure. We summarize the contrasting effects of efficiency on capital structure in terms of two competing hypotheses: the efficiency-risk and franchise-value hypotheses. Using quantile regressions we test the effect of efficiency on leverage and thus the empirical validity of the two competing hypotheses across different capital structure choices. We also test the direct relationship from leverage to efficiency stipulated by the Jensen and Meckling (1976) agency cost model. Throughout this analysis we consider the role of ownership structure and type on capital structure and firm performance.